Challenging Secularism: Considering Islam and State in Indonesia - Zaenal Muttaqin (Universitas Darussalam Gontor, 2010)
This paper discussed the encounter of Indonesian Muslims toward the idea of secularism. Secularism since its rise in Europe in the 18th century has spread all over the world. Supporters of secularism have assumed that secularism is undeniable. People eventually will hold it and apply it in their life, including in the public space. However, in the context of the relationship between Islam and state in Indonesia, secularism thesis has been proven failed. During the Indonesian history, the relationship between Islam and state has been a hot discourse even until recently. Yet, this paper concluded that one thing is clear; Indonesian people, especially Indonesian Muslims, have rejected secularism. In the meantime, some have rejected theocratic state either. Muslims then have endlessly endeavored to reformulate a viable synthesis on the relationship between Islam and state in Indonesia. What Indonesia has now is among the efforts of Indonesian Muslims to have a better formulation on how Islam plays its role in the public space, including in the political sphere.